Problems of writing on digital surfaces in online handwriting recognition systems - Abuzaraida, Mustafa Ali; Zeki, Akram M.; Zeki, Ahmed M. (2013)
Nowadays, keyboards and mice are the basic input devices for personal computers. Nevertheless, these devices may not remain as the only way of transmitting electronic data to computers. Other methods may become necessary, particularly with regard to the size of newer mobile devices and the method of transmission. Hand-held computers, mobile technology, for example, present significant opportunities for alternative devices that work in forms smaller than the traditional keyboard and mouse. In addition, the need for more natural human-machine interfaces becomes more important due to computer usage reaches a larger number of people worldwide. However, these new ways of human-machine interfaces have some problems while connecting to the computers. This paper presents and highlights some of these problems in the field of script recognition. This paper also illustrates the used techniques to overcome these matters.